HUBUNGAN SELF-EFFICACY DAN SELF-REGULATED LEARNING SISWA SMA KELAS XII - Sulaeman, Riemaya Martiza; Syamsuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The complexity of mathematics material at the high school level demands not only cognitive abilities but also support from affective and regulatory factors, particularly self-efficacy and self-regulated learning (SRL). This study employed a quantitative approach with a correlational design among a population of 12th-grade students at MAN 2 Jakarta, with a sample of 64 12th-grade students selected through purposive sampling based on their engagement in learning integral calculus material. Data were collected using a Likert-scale questionnaire that met high validity and reliability standards (Cronbach’s Alpha = 0.91). Spearman’s rank correlation analysis revealed a positive and significant relationship between self-efficacy and SRL (r = 0.577; p < 0.001). These results indicate that the higher students’ self-efficacy, the better their SRL skills in mathematics learning. These findings affirm the role of self-efficacy as an important psychological factor in supporting SRL, thus the strengthening of self-efficacy needs to be integrated into mathematics learning strategies at the high school level.